Elements of war crimes under the Rome Statute of the International Criminal Court : sources and commentary - Dörmann, Knut (Cambridge University Press, 2003)
The Elements of War Crimes will assist the International Criminal Court (ICC) in the interpretation and application of the articles of the ICC Statute defining the crimes under its jurisdiction. These will not only be necessary for the future work of the ICC in interpreting the crimes provisions, but also for national courts, which have primary responsibility in the prosecution of international crimes under the Rome Statute. This commentary provides a critical insight into the travaux prep?aratoires of the Preparatory Commission leading to the adoption of the elements of war crimes. It contains an analysis of existing case law related to each war crime in the Statute. It will provide States, judges, prosecutors and international and national lawyers with key background information to implement international humanitarian law in future cases dealing with war crimes under the ICC. A unique, indispensable tool for prosecuting and defense lawyers working in international criminal law.